2019
DOI: 10.1111/febs.15167
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for GTP recognition by light‐activated guanylate cyclase RhGC

Abstract: Cyclic guanosine 3 0 ,5 0-monophosphate (cGMP) is an intracellular signalling molecule involved in many sensory and developmental processes. Synthesis of cGMP from GTP is catalysed by guanylate cyclase (GC) in a reaction analogous to cAMP formation by adenylate cyclase (AC). Although detailed structural information is available on the catalytic region of nucleotidyl cyclases (NCs) in various states, these atomic models do not provide a sufficient explanation for the substrate selectivity between GC and AC fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Previous studies demonstrated that the N-terminus plays a crucial role for the catalytic activity of RGCs, and both C-terminal and N-terminal GC interactions have been proposed ( Scheib et al, 2018 ; Butryn et al, 2020 ). Therefore, we analyzed different truncations to elucidate potential structure rearrangements in the linker and N-terminal region during photoactivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that the N-terminus plays a crucial role for the catalytic activity of RGCs, and both C-terminal and N-terminal GC interactions have been proposed ( Scheib et al, 2018 ; Butryn et al, 2020 ). Therefore, we analyzed different truncations to elucidate potential structure rearrangements in the linker and N-terminal region during photoactivation.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies confirmed its function as a photoactivated guanylyl cyclase that is inactive in the dark and fully active when illuminated with green light ( Scheib et al, 2015 ). More functional details are available from the orthologous protein of the related fungus Catenaria anguillulae ( Ca RGC) including the crystal structure of the constitutively active isolated cyclase domain ( Scheib et al, 2018 ; Butryn et al, 2020 ). The results show the photoreceptor to assemble as a homodimer, with the rhodopsin modules responsible to silence the cyclase activity in darkness.…”
Section: Introductionmentioning
confidence: 99%
“…The rhodopsins consisting of seven transmembrane α-helices belong to the vast family of G protein-coupled receptors [ 324 , 368 ]. The light-induced isomerisation of the 11-cis-retinal is coupled to a cascade of events that relay the signal to guanylate kinases [ 369 , 370 ] or phosphodiesterase [ 371 ] that trigger various intracellular responses. The PYP adopt the fold of the Per-ARNT-Sim (PAS) domain [ 372 , 373 ] that senses a vast range of stimuli, from photon to ligand [ 374 ].…”
Section: Cell Signalling and Sensory Motricitymentioning
confidence: 99%
“…Rhodopsin consisting of seven trans-membrane α-helices belongs to the vast family of G-protein-coupled receptors [ 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. The light inducing isomerization of the 11-cis-retinal is coupled to a cascade of events that ultimately acts as a switch to relay the signal to G-proteins [ 106 , 107 ], guanylate kinases [ 101 , 108 ] or phosphodiesterase [ 102 ] that triggers various intracellular responses. Sensory rhodopsins that are responsible for light signalling and photo-behaviours have been found in archaea and bacteria [ 109 , 110 , 111 , 112 ].…”
Section: Introductionmentioning
confidence: 99%